A Survey on National Pediatric Antibiotic Stewardship Programs, Networks and Guidelines in 23 European Countries. Issue 11 (November 2020) - Kopsidas, Ioannis; Vergnano, Stefania; Spyridis, Nikos; Zaoutis, Theoklis; Patel, Sanjay
Abstract : Background: Misuse, overuse of antimicrobials and increasing rates of antimicrobial resistance are well-recognized problems throughout Europe. The aim of this survey was to describe the current pediatric antibiotic stewardship (PAS) landscape across Europe and identify gaps, in terms of national programs, networks and guidelines. Methods: A survey of 17 questions was circulated in July 2019 among 24 European pediatric infectious disease researchers and clinicians, professors and heads of department on the existence of PAS programs, national networks and meetings, established competencies, metrics and guidelines. Results: We received responses from 23 countries. National guidelines on the management of children with common infections treated in hospital settings exist in 15 of 23 (70%); only 8 of 15 (53%) had been updated within the previous 4 years. Most provide guidance on antibiotic initiation and duration (14 of 15, 93%), but few on when to transition from intravenous to oral antibiotics (7 of 15, 47%). National PAS competencies have only been developed in 4 countries; only 1 addressed both community and hospital prescribing. Organized national PAS networks are only established in the United Kingdom and Germany; 21 of 23, 91% countries had no agreed metric for antibiotic prescribing in children; 2 of 23 were based on daily defined doses. Conclusions: Fragmented implementation of PAS programs, no agreed metrics, lack of established PAS competencies and national PAS networks along with inexistent funding is alarming in view of existing high rates of antimicrobial resistance in Europe. Abstract : Supplemental Digital Content is available in the text.